Outcome Evaluation of the Public Management Development Program - Sonny N. Domingo; Michael Ralph M. Abrigo; Charlotte Justine Diokno Sicat; Perla U. S. Bernardo; Mary Pauline V. Saquing; John Joseph S. Ocbina (Philippine Institute for Development Studies (PIDS), 2022)
The Public Management Development Program (PMDP), the National Government Career Executive Service Development Program (NGCESDP), was revitalized in 2012 through Republic Act 10155 or the General Appropriations Act of 2012. The Program is the government's response to the government's aim of professionalizing the bureaucracy and the call for ethical, honest, and effective public governance. The Development Academy of the Philippines (DAP) acts as the implementing agency of the Program. Currently, the Program offers four courses: the Middle Managers Class (MMC), the Senior Executives Class (SEC), the Phronetic Leadership Class (PLC), and the Local Government Executives and Managers Course (LGEMC). The results of the outcome evaluation of the PMDP, which used both qualitative (surveys and key informant interviews) and quantitative (quasi-experimental statistical matching and difference-in-difference) methods, show positive indications of improvement in the CES competencies of the PMDP graduates, as well as their individual and organizational impact and phronetic leadership traits. However, there is less convincing evidence regarding their networking and innovation skills. The quantitative and qualitative evaluations of the scholars' individual competences and organizational contributions lead to favorable outcomes due to the Program, despite areas for improvement in the PMDP's implementation being noted.
Keywords: 330; Public Management Development Program; bureaucracy; outcome evaluation; CESB competencies; Phronetic leadership; average treatment effect; difference-in-difference